Rough waters : nature and development in an East African marine park - Walley, Christine J., 1965- (Anthropology online., 2004)
Rough Waters explores one of the most crucial problems of the contemporary era--struggles over access to, and use of, the environment. It combines insights from anthropology, history, and environmental studies, mounting an interdisciplinary challenge to contemporary accounts of ""globalization."" The book focuses on The Mafia Island Marine Park, a national park in Tanzania that became the center of political conflict during its creation in the mid-1990s. The park, reflecting a new generation of internationally sponsored projects, was designed to encourage environmental conservation a.